Course alignment: Application and revision of a method to align a course - Alandia Robles, Gabriela (Improving University Science Teaching and Learning, 2023)
The course alignment is important to set up the desired outcomes of teaching in terms of contents and also level of understanding that we want students to achieve (Biggs, 2003). The course alignment should use the objectives or learning outcomes of the course as the driving force to plan teaching, learning and assessment activities. The course alignment should help to guide students with a clear direction and to improve learning experiences. Considering constructive alignment, a good structure of the course depends on consistency between the objectives, content, learning activities and assessment methods. It can constitute a good tool of communication with students to clarify expectations, reduce anxiety and give more sense of the course into the program (Biggs, 2014; Blumberg, 2009)